Pattern recognition of acorns from different Quercus species based on oil content and fatty acid profile - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M.F. F (Grasas y Aceites, 2007)
The aim of this study was (i) to characterize different species of Quercus genus and (ii) to discriminate among them on the basis of the content and fatty acid composition of the oil in their fruits and/or their morphological aspects via pattern recognition techniques (Principal Component Analysis, PCA, Cluster Analysis, CA, and Discriminant Analysis, DA). Quercus rotundifolia Lam., Quercus suber L. and Quercus pyrenaica Willd., grown in the same stand in the centre of Portugal, were investigated. When oil content and respective fatty acid composition were used to characterize samples, well-separated groups corresponding to each of the species were observed by PCA and confirmed by CA and DA. The ‘‘width’’ and ‘‘length’’ of acorns exhibited a low discriminant power. Acorns from Q. rotundifolia showed the highest average oil content followed by Q. suber and Q. pyrenaica acorns (9.1, 5.2 and 3.8%, respectively). Fatty acid profiles of Q. rotundifolia and Q. suber oils are similar to olive oil while the oil from Q. pyrenaica acorns is more unsaturated
Keywords: acorn; cluster analysis; Discriminant analysis; Oil; Principal component analysis; Quercus

Pattern recognition of acorns from different Quercus species based on oil content and fatty acid profile - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M. F. F. (Grasas y Aceites, 2007)
The aim of this study was (i) to characterize different species of Quercus genus and (ii) to discriminate among them on the basis of the content and fatty acid composition of the oil in their fruits and/or their morphological aspects via pattern recognition techniques (Principal Component Analysis, PCA, Cluster Analysis, CA, and Discriminant Analysis, DA). Quercus rotundifolia Lam., Quercus suber L. and Quercus pyrenaica Willd., grown in the same stand in the centre of Portugal, were investigated. When oil content and respective fatty acid composition were used to characterize samples, well-separated groups corresponding to each of the species were observed by PCA and confirmed by CA and DA. The ‘‘width’’ and ‘‘length’’ of acorns exhibited a low discriminant power. Acorns from Q. rotundifolia showed the highest average oil content followed by Q. suber and Q. pyrenaica acorns (9.1, 5.2 and 3.8%, respectively). Fatty acid profiles of Q. rotundifolia and Q. suber oils are similar to olive oil while the oil from Q. pyrenaica acorns is more unsaturated
Keywords: acorn; cluster analysis; Discriminant analysis; Oil; Principal component analysis; Quercus